(untitled) (Global Journal of Human-Social Science, 2020)
This study investigated the perceived influence of skills acquisition programmes on the socioeconomic development of women in Andoni Local Government Area, Rivers State. The study was guided by five research objectives, five research questions, and four null hypotheses which were tested at 0.05 significant levels. The study adopted a descriptive survey design. The population for this study comprised 742 trainees in 20 functional skills acquisition training programmes, out of, which 371 trainees in 20 functional skills acquisition training programmes were selected through a proportionate sampling technique. A validated questionnaire titled "Perceived Influence of skills acquisition programme on Socio-Economic Development of Women" with a reliability index of 0.83 was used for data collection. Mean and standard deviation was used to analyse data collected. The findings revealed that skills acquisition programmes had influenced their socio-economic life by providing them with life-changing skills for selfreliance and improved women social status.